2021
DOI: 10.1111/coa.13774
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives on recall period and response options in patient‐reported outcome measures for chronic rhinosinusitis symptomatology: A pilot study

Abstract: Objective Patient‐reported outcome measures (PROMs) for assessment of chronic rhinosinusitis (CRS) employ a variety of recall periods and response scales for reporting CRS symptom burden. CRS patient perspective is unknown with respect to recall periods and response scales in PROMs. Design Cross‐sectional study. Setting Tertiary rhinology clinic. Participants Sixty three adults with CRS. Main outcome measures Participants were asked to choose which CRS symptom recall period—1 day, 2 weeks, 1 month or greater t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The importance of stakeholder involvement (i.e., patients and healthcare professionals) during PROM development and refinement has been outlined. 44,[46][47][48] The involvement of clinicians and researchers is of particular importance for determining which items to use or eliminate in a well-established PROM, such as the SNOT-22. Although considering psychometric properties and evidence (data-driven approach) is undoubtedly helpful for PROM development, stakeholders' perspectives must also be considered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The importance of stakeholder involvement (i.e., patients and healthcare professionals) during PROM development and refinement has been outlined. 44,[46][47][48] The involvement of clinicians and researchers is of particular importance for determining which items to use or eliminate in a well-established PROM, such as the SNOT-22. Although considering psychometric properties and evidence (data-driven approach) is undoubtedly helpful for PROM development, stakeholders' perspectives must also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of patient perspectives in the technical aspects of CRS PROM design have been missing and have only recently been shown to provide novel insights into how CRS PROMs could more accurately reflect patients' disease burdens and how PROM results may most inform clinical decision-making. 48 Therefore, it is clear that IRT will not be the final answer to SNOT-22 development and refinement (or for any PROM) entirely on its own, because important stakeholder information (such as from patients or healthcare professionals) still needs to be considered. Nonetheless, we believe that an IRT-based approach provides a starting point from which further development and refinement steps may profit, with the goal to increase the utility of the SNOT-22 in both clinical and research settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we assessed the validity of patient-reported CRS disease control on a 1-month time scale to be consistent with the recall period used to assess CRS symptoms by EPOS CRS disease control guidelines. However, more recent work by our group has also suggested that a 1-month recall period for CRS disease burden may best balance patients' confidence in their recall ability as well as balance patient perspectives on timescales to be used for assessment of their current disease state as well as for clinical decision-making with respect to treatments including endoscopic sinus surgery (40) .…”
Section: Discussionmentioning
confidence: 99%